Serviceology for Services Selected papers of the 1st International Conference of Serviceology - Mochimaru, Masaaki; Ueda, Kanji; Takenaka, Takeshi (Springer Japan : Imprint: Springer, 2014)
Services are key activities in the globalization of the economy and also underlie the quality of life of local residents. The advanced work presented in this book was selected from the proceedings of the First International Conference on Serviceology (ICServ2013), held October 16-18, 2013 in Tokyo. This book provides a useful overall guide to the state of the art in theory and practice of services for researchers in various fields, including engineering, marketing, economics, and others. This work also facilitates the scientific systematization of services and promotes technological developments for solutions of industrial issues.